Islam and Local Wisdom: The Mangalap Tukkot Marriage Tradition in the Angkola Batak Community - Ihwan Sormin (Hukum Keluarga Islam IAIN LANGSA, 2023)
The mangalap tukkot tradition is a polygamous tradition that can be carried out by the husband if the wife cannot give birth. This tradition is often carried out without permission from the court, as stipulated in statutory regulations. In addition, this tradition also does not involve the results of a medical examination that determines which party cannot give birth. This study aims to analyze how Islamic law views the mangalap tukkot tradition, which is rooted in the practice of marriage in the Angkola community. This research resulted from empirical studies with data collection techniques in the form of interviews and observations. Approach Juridis is used in this study to examine, from the perspective of Islamic law, the tradition of mangalap tukkot. The results of the study show that the mangalap tukkot tradition is normatively in accordance with Islamic law because, in Islam, the reason for not having children is permissible for polygamy. However, when viewed from the maslahah aspect, the mangalap tukkot tradition is not in accordance with the principles of justice for women because it tends to position the wife as a subordinate in matters of marriage. This makes the assumption that women are merely a complement to the interests of men. And this is really contrary to Islamic principles, which prioritize human values like justice, equality, and benefit.